«HEAD/BAS» KOMPONENTLI FRAZEOLOGIYALÍQ BIRLIKLERDIŃ EKSPRESSIV-METAFORALÍQ SÍPATÍ - Arzimbetova, S.A. (SCIENCE and SOCIETY, 2025)
This article explores the structure of phraseological units and their semantic implications. It differentiates between neutral and expressive-metaphorical units. The research provides a comparative analysis of phraseological units containing the “head” component in Karakalpak and English. The findings contribute to a deeper understanding of phraseological meanings and their contextual usage.